Jurisprudential Questions of the Companions the Mother of the Believers Aisha Through the two Sahihs in the Chapter on Prayer - a Comparative Jurisprudential Study - - Muhanna , Ahmed (Islamic Sciences Journal, 2023)
I have shown in this research the status of the Companions, may Allah be pleased with them, and their favor and jurisprudence, due to their closeness to the Prophet, may Allah’s prayers and peace be upon him, They used to ask the Prophet during his life among them about matters of religion and when he moved to the Supreme Companion they asked his wives, and the best of his wives, peace and blessings be upon them, is a mother of Believers Aisha, may Allah be pleased with her, is one of the companions ’jurists and teaches them the rulings of religion. I initiated the research with an introduction which indicates the significance of the research , the reason behind selecting it and its produces. I have divided this research into two parts. In the first part , I presented the companions , their position and Mrs. Aisha, her merits, jurisprudence, and position. Moreover, I have presented the most correct book after The Book of Allah Almighty and they are the two Sahihs, Sahih al-Bukhari and Sahih Muslim. I became acquainted with them and the reasons for their authorship. It was studied by a comparative jurisprudential investigation, and the research was concluded with a conclusion, sources and references.